Dementia and depression in older adults: a southeast European perspective: summary of a dementia psychogeriatric symposium held in Ohrid, Macedonia, 23 May 2013 - Mukaetova-Ladinska, Elizabeta B; Krsteska, Roza; Vaskova, Olivija; Makazlieva, Tanja; Tsolaki, Magda (My University, 2014)
We present a report on the recent symposium on dementia and depression in older adults, held in Ohrid, Macedonia and discuss the urgent need for development of psychogeriatric and affiliated services in the Southeast European region. The limited epidemiological data from nine countries in this region suggest high variability of prevalence rates for mental health problems in older adults (>65 years of age). At the moment, there are over 520,000 older adults in the region living with dementia alone. The prevalence rates for dementia (%) are either similar to those of the developed countries (9-9.6% in build-up northern Greece and Albania, respectively) or substantially lower (3.6-4% in rural northern Greece and Montenegro, respectively). The latter may be due to either cultural diversity or lack of adequate medical health service provision and expertise to recognize and diagnose dementia. Indeed, there is a lack of organized specialized services for older adults with mental health problem in the region. The symposium raised the awareness of this problem in the region and called for networking between isolated individuals working in this field to improve the current situation and facilitate further development of adequate clinical services to meet the growing needs of the older adults in the countries of the Southeast Europe.